Association of Fut1 and Slc11a1 gene polymorphisms with productivity traits of Large White pigs - Sukhno, V. V.; Vashchenko, P. A.; Saenko, A. M.; Zhukorskyi, O. M.; Tserenyuk, O. M.; Kryhina, N. V. (Regulatory Mechanisms in Biosystems, 2022)
The purpose of our work was to study the polymorphism of genes associated with disease resistance and to search for their associations with productive traits in the population of the Ukrainian Large White pigs. For this study, 50 pigs were used, observations and measurements were carried out at the age from birth to 180 days. Genetic studies were carried out in a certified laboratory of the Institute of Pig Breeding and Agroindustrial Production. In the study of fucosyltransferase 1 and solute carrier family 11 member 1 genes, polymorphism was found in three of the five analyzed loci. In the Ukrainian Large White subpopulation of pigs the informativeness of these gene polymorphisms was at the optimal level for associative analysis, Polymorphism Information Content was greater than 0.3 in two loci. A sufficiently high level of Polymorphism Information Content indicates the value of this breed to preserve the biodiversity of pigs. The distribution of genotypes at some loci of the solute carrier family 11 member 1 gene was characterized by a deviation from the theoretically expected one due to the increase in the frequency of the heterozygous genotype. There was also a statistically confirmed deviation of the genotypes’ distribution from the normal and polymorphism fucosyltransferase 1 gene, but in this case in the direction of increasing the frequency of both homozygous variants. These results indicate the presence of a certain selection pressure on the mentioned polymorphisms and their possible impact on productive traits. The influence of solute carrier family 11 member 1 gene polymorphism on the weight of pigs at the age of 120 and 180 days, the average daily gain recorded in the period 28–120 days and from birth to 180 days, as well as on the backfat thickness, was established. The preferred genotype is TT, which can be used in breeding to obtain more productive animals with increased disease resistance, but in the selection of animals at this locus, it is necessary to control the backfat thickness and prevent breeding of pigs that may worsen this trait.